Viabilitas Spermatozoa Semen Beku Babi Duroc Dalam Extender Beltsville Thawing Solution Menggunakan Krioprotektan Gliserol Dan Dimetillacetamida - Nancy D. F. K. Foeh; Raden Iis Arifiantini; Tuty Laswardy Yusuf (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
This study investigated the effect of glycerol and dimethylacetamide (DMA) in beltsville thawing solution (BTS) extender. Semen samples were collected from three boars of the Duroc breed (n=5) and were evaluated microscopically and macroscopically. Semen that have been evaluated and meets the following criteria: has motility characteristics >70%, concentration >300 million/ml and abnormality 20%; was accepted as appropriate samples. Semen samples were divided into four tubes and were diluted with 5 ml of BTS. The diluted semen was left for two hours in the temperature range from 20 to 22°C before was centrifuged for 15 minutes (500G). The pellet of centrifuged semen was taken as much as 1 ml with its supernatant. The BTS glycerol (BTSG), BTS-DMA (BTSD), BTS-Glycerol-DMA (BTSG-D) were added into the pellet. The diluted semen was packed into straw of 0.5 ml and was equilibrated for 2 hours in 4 °C. The equilibrated semen was frost with the steam of nitrogen and stored in liquid nitrogen. The quality of frozen semen was assessed at least 24 hour after freezing process. The results indicate that the sperm motility after thawing in BTS extender BTSD is 52.14±0.4%, ,higher than the other two extenders (P<0.05). Thus, it is conclude that the DMA concentration in BTS extender maintains the quality of frozen semen from the Duroc breed better than other extenders.